1991
DOI: 10.1001/archsurg.1991.01410310059008
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Evaluation of Henoch-Schönlein Purpura Experience With 110 Children

Abstract: Henoch-Schönlein purpura is a disorder of unknown origin that is probably related to an autoimmune phenomenon. This report concerns 110 children (mean age, 6.2 years; range, 6 months to 14 years) with Henoch-Schönlein purpura. Seventy-two (65%) had abdominal pain associated with nausea and vomiting, bloody stool, and upper gastrointestinal bleeding. Sixty patients with abdominal pain were evaluated and treated conservatively. However, 12 patients underwent laparotomy. Six underwent unnecessary appendectomy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
14

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 24 publications
0
64
0
14
Order By: Relevance
“…One of the cases underwent colonoscopy, and intussusception was reduced by colonoscopic insufflation [13] . In contrast, intestinal ischemia, perforation, hemorrhage, fistulas, pancreatitis, and appendicitis are rare [9,14] . However, Zhang et al [10] in their assessment of adult patients with gastrointestinal manifestations of HSP showed that the first symptoms may appear as "acute abdomen" without lesions, and that gastroscopy and colonoscopy may be helpful in early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the cases underwent colonoscopy, and intussusception was reduced by colonoscopic insufflation [13] . In contrast, intestinal ischemia, perforation, hemorrhage, fistulas, pancreatitis, and appendicitis are rare [9,14] . However, Zhang et al [10] in their assessment of adult patients with gastrointestinal manifestations of HSP showed that the first symptoms may appear as "acute abdomen" without lesions, and that gastroscopy and colonoscopy may be helpful in early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bu yüzden akut skrotum yapan sebeplerden HSP'nin varlığını bilmek önemlidir. Önceki serilere bakıldığında HSP'ye bağlı akut skrotum gelişen olgularda cerrahi eksplorasyon uygulandığı görülmektedir (2,3,6) . Soreide ve ark.…”
Section: Discussionunclassified
“…As an optional application, CE can be applied to evaluate the management of gastrointestinal diseases such as Henoch-Schonlein purpura (HSP) (Preud'Homme DL, 2006) and GVHD (Silbermintz, 2006;Yakoub-Agha I, 2004). In HSP, sastrointestinal bleeding occurs in ~50% of children, and massive bleeding may occur (Katz, 1991). A previous report demonstrated that CE contributed to identify the extent of the small intestinal involvement of HSP and confirmed the efficacy of cyclophosphamide therapy in improving the gastrointestinal lesions (Preud 'Homme DL, 2006).…”
Section: Othersmentioning
confidence: 99%